IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA PADA BIRO UMUM SEKRETARIAT DAERAH PROVINSI LAMPUNG - Agus Purnomo; Muhammad Yuliardi (Universitas Bandar Lampung (UBL), 2021)
The problems in this study are (1) How is the Implementation of Human Resource Development in the General Bureau of the Regional Secretariat of Lampung Province? (2) What aspects are the supporters and obstacles in the Implementation of Human Resource Development at the General Bureau of the Regional Secretariat of Lampung Province?The method used in this research is descriptive qualitative research method. The use of this method is to describe the implementation of Human Resource Development in the General Bureau of the Regional Secretariat of Lampung Province, to examine qualitatively, how all data were obtained directly from informants in the field using interviews and document studies.The results showed that the Implementation of Human Resource Development Policies at the General Bureau of the Regional Secretariat of Lampung Province, through (1) Education, in general employees still have high school education, (2) Training, has been carried out but not all employees have followed suitably. routine, (3) Skills, in general employees have good work skills, although not optimal.Supporting aspects (1) Every employee is given the opportunity to attend formal education, (2) Every employee is given the opportunity to participate in training activities, (3) There is a desire for employees to develop themselves. While the inhibiting aspects are (1) existing human resources, generally having a high school (SMA) educational background, (2) lack of budget supporting education and training to the empoyee at The Bureau of General Secretariat of Lampung Province